MEDIASI KESALEHAN SELEBRITI PEREMPUAN HIJRAH DI MEDIA SOSIAL INSTAGRAM - Siti Machmiyah (Widya Komunika, 2020)
ABSTRACT The group of people who call themselves 'hijrah' in the realm of Islam has indeed become a new trend in Indonesia. This cannot be separated from the influence of post-Islamism which is rife where the traditional elements (in this case religion) can go hand in hand with the elements of modernity. Hijrah becomes a form of popular culture that can be easily followed by some Indonesian people, including by female celebrities, they eventually become a new 'capital' among bearers of hijrah because celebrities have a strong magnet to be a Hijrah trendsetter only close to the da’I who is a role model. The celebrities who hijrah were inevitably packing themselves to become the perfect celebrity hijrah figure, one of which was by branding the hijrah on Instagram social media, the hijrah celebrity then mediated ‘piety’ on Instagram through three things; upload preaching message content in everyday life, Islamic lifestyle in marketing endorsement products, and do remediation of preaching content from the da'i they follow. Keywords : Celebrity, Hijrah, mediation